그레고리 베이트슨의 이중구속의 선물(Gift)과 메타커뮤니케이션의 논리 - 정재식 (영어영문학, 2020)
Through deep reading of Gregory Bateson’s Steps to Ecology of the Mind, this paper examines the dynamic interactions of “pathology and the creativity” inherent in the gift of the double bind and the philosophical core of the meta-communication that can transform double the bind into force of healing and creation. This double bind, which embodies logical contradiction, and paradox and triggers conflicting emotions and acts, can be compared to be a “pathless”(road-less) situation in which an escape is impossible. It is generated by the “two contradictory messages”(injunctions) imposed by multi-layered communication. Bateson warns that such continued exposure to the “unsolvable chain of experiences” could lead to serious distortions and cracks in the victim’s self-correcting system of thought and emotion, which can drive him or her to schizophrenia. He proposes meta-communication as a therapeutic and productive communication method to solve the pathology of double-binding while maximizing the creativity contained within the double bind. Meta-communication is a meta-reflection and communication ability that can enhance our understanding of ourselves, the other, and the world by viewing our world from higher, wider and more diverse perspectives. This meta-communication can provide us with a superior capacity to come up with creative responses and acts that can be worthy of what happens to us in the situation of the double bind. In that sense, this communication ultimately becomes the core of the wisdom of life, which carries out an inventive combination of theory and practice, and goes beyond the realm of knowledge.
Keywords: Gregory Bateson; double bind; pathology; creativity; meta-communication; 그레고리 베이트슨; 이중구속; 병리적; 창조성; 메타커뮤니케이션